2021
DOI: 10.1002/ijgo.13633
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the COVID‐19 pandemic on the postpartum course: Lessons learnt from a large‐scale comparative study in a teaching hospital

Abstract: Objective To evaluate the consequences of COVID‐19 pandemic restrictions on the postpartum course. Methods A retrospective cross‐sectional study compared women who gave birth between March and April 2020 (first wave), between July to September 2020 (second wave), and a matched historical cohort throughout 2017–2019 (groups A, B, and C, respectively). Primary outcomes were postpartum length of stay (LOS), presentations to the emergency department (ED), and readmissions 30 days or longer after discharge. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Our results show a reduction in prolonged maternal hospital stays, a finding supported by other studies [ 44 46 ]; early discharge from the hospital may have been initiated by either the clinician or the woman to reduce the perceived risk of infection associated with hospital stay, or to reunite with family members unable to visit maternity units. Rates of maternal readmission were also reduced during the pandemic period, which may reflect that women were less likely to seek care for postpartum issues.…”
Section: Discussionsupporting
confidence: 89%
“…Our results show a reduction in prolonged maternal hospital stays, a finding supported by other studies [ 44 46 ]; early discharge from the hospital may have been initiated by either the clinician or the woman to reduce the perceived risk of infection associated with hospital stay, or to reunite with family members unable to visit maternity units. Rates of maternal readmission were also reduced during the pandemic period, which may reflect that women were less likely to seek care for postpartum issues.…”
Section: Discussionsupporting
confidence: 89%
“…Another study found that though women were discharged from the hospital on average 24 hours earlier during the pandemic than before its onset, emergency department visits and readmissions among postpartum women remained the same. The authors suggested that shorter postpartum stays may therefore represent a cost-effective alternative to pre-pandemic practice (Kugelman et al, 2021). Aside from this study, our review of the literature found no other studies examining postnatal care for mothers not infected with COVID-19 and their families during the pandemic.…”
Section: Introductionmentioning
confidence: 67%
“…Interestingly, expedited discharge was not one of the hospital policies implemented during their study period to decrease SARS-CoV-2 transmission. The second, a study by Kugelman et al, 27 from a delivery hospital in Israel, examined a cohort of 3,377 obstetric patients and similarly found a decrease in postpartum hospitalization LOS and no difference in hospital readmission within 30 days of discharge. The third study, from a health system in New York, 28 also reported a decrease in postpartum LOS; however, adverse outcomes were not reported.…”
Section: Discussionmentioning
confidence: 99%